PENGARUH BUDAYA ORGANISASI, PELAKSANAAN TANGGUNG JAWAB, OTONOMI KERJA, DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR (Studi Pada Kantor Akuntan Publik di Jakarta) - Syauffa Pratiwi; Reskino Reskino (Akuntabilitas, 2016)
This research purposed to examine the effect of organizational culture, exercised responsibility, job autonomy and role ambiguity to job performance auditor. Respondents in this research were auditors who work in public accounting firms in Jakarta. Based on purposive sampling method, total sample in this research was 133 respondents of 33 public accounting firms in Jakarta. Hypothesis in this research used multiple regression analysis.The results of this research indicate that organizational culture, exercised responsibility, and job autonomy positive and significant effect on job performance auditor, while role ambiguity based on data collected failed to prove the link between the ambiguities of the role and performance of auditors. Or in other words, the sample can not be generalized to the study population.DOI: 10.15408/akt.v9i1.3585